Hubungan Kehamilan Ibu Usia Dini dengan Kejadian Stunting Pada Balita di Wilayah Kerja Puskesmas Bambulung Kabupaten Barito Timur - Ane, Jeane Nadya Handriani; Syamsul Arifin; I Gde Hary Eka Adnyana (Fakultas Kedokteran Universitas Palangka Raya, 2023)
The prevalence of stunting under five in Central Kalimantan is, 27,7%, where East Barito Regency is in the second highest position with 33,7%. This makes East Barito Regency one of government’s priority targets in tackling the high incidence of stunting in Central Kalimantan. The sub-district that is the main priority of the East Barito Regency government in interventing stunting events is Pematang Karau District. This study aims to determine the relationship between young mothers pregnancy and the incidence of stunting in children under five in the working area of Bambulung Public Health Center, East Barito Regency. This research uses analytical observation method using case control. Sampling was done by purposive sampling method. The statistical test used is the chi-square test. In this study, 39 stunted toddlers were used as the case group and 30 non-stunted toddlers as the control group. Where there are 25 (41,70%) respondents of young mothers pregnancy at an early age (<20 years) in the case group as many as 18 (30,00%) and in the control group as many as 7 (11,70%). Then, non-young mother’s pregnancy 35 (58,30%) respondent consisting of 12 (20,00%) respondents frim the case group and as many as 23 (38,30%) from the control group. The result of the chi-square test obtained p=0,009, OR =4,929, CI 95% =1,612-15.071. There is a significant relationship between young mothers pregnancy and the incidence of stunting in children under five in the working area of the Bambulung Public Health Center, East Barito Regency and early pregnancy risks of 4,929 times greater risk of stunting in children under five compared to early age mothers.